SISTEM INFORMASI SURAT KETERANGAN PENDAMPING IJAZAH (SKPI) BERBASIS WEB PADA KAMPUS X - Fikri Zukri; Tina Tri Wulansari; Riyayatsyah (METIK JURNAL, 2020)
In making the information system of diploma companion certificate (SKPI) BAAK Campus X there was a pile up of files to overcome these problems, so a certificate of companion certificate information system (SKPI) was made on Campus X based on website.. The System Development Method used in this thesis is the Prototype Method while the tool used in the development of the thesis system is Flowchart, FOD, CD, DFD, Relationship Tables and table structure as well as Making a system using the PHP Programming language and MySQL database management system Beta test results show that 67% of respondents said that this system fulfills 9 criteria for a good website. 100% of respondents (BAAK administrators) said that this system helped BAAK work. (FZ).